A hierarchical network of hypoxia-inducible factor and SMAD proteins governs procollagen lysyl hydroxylase 2 induction by hypoxia and transforming growth factor β1 - Rosell-García, Tamara (J Biol Chem, 2019)
Collagens are extracellular matrix (ECM) proteins that support the structural and biomechanical integrity of many tissues. Procollagen-lysine, 2-oxoglutarate 5-dioxygenase 2 (PLOD2) encodes the only lysyl hydroxylase (LH) isoform that specifically hydroxylates lysine residues in collagen telopeptides, a post-translational modification required for the formation of stabilized cross-links. PLOD2 expression is induced by hypoxia and transforming growth factor-β1 (TGF-β1), well-known stimuli for the formation of a fibrotic ECM, which can lead to pathological fibrosis underlying several diseases. Here, using human and murine fibroblasts, we studied the molecular determinants underlying hypoxia– and TGF-β1–induced PLOD2 expression and its impact on collagen biosynthesis. Deletion mapping and mutagenesis analysis identified specific binding sites for hypoxia-inducible factors (HIF) and TGF-β1–activated SMAD proteins on the human PLOD2 gene promoter that were required for these stimuli to induce PLOD2 expression. Interestingly, our experiments also revealed that HIF signaling plays a preponderant role in the SMAD pathway, as intact HIF sites were absolutely required for TGF-β1 to exert its effect on SMAD-binding sites. We also found that silencing PLOD2 expression did not alter soluble collagen accumulation in the extracellular medium, but it effectively abolished the deposition into the insoluble collagen matrix. Taken together, our findings reveal the existence of a hierarchical relationship between the HIF and SMAD signaling pathways for hypoxia– and TGF-β1–mediated regulation of PLOD2 expression, a key event in the deposition of collagen into the ECM.